National and subnational all-cause and cause-specific child mortality in China, 1996–2015: a systematic analysis with implications for the Sustainable Development Goals - He, Chunhua; Liu, Li; Chu, Yue; Perin, Jamie; Dai, Li; Li, Xiaohong; Miao, Lei; Kang, Leni; Li, Qi; Scherpbier, Robert; Guo, Sufang; Rudan, Igor; et al. (The Lancet global health, 2017)
China has achieved Millennium Development Goal 4 to reduce under-5 mortality rate by two-thirds between 1990 and 2015. In this study, we estimated the national and subnational levels and causes of child mortality in China annually from 1996 to 2015 to draw implications for achievement of the SDGs for China and other low-income and middle-income countries. In this systematic analysis, we adjusted empirical data on levels and causes of child mortality collected in the China Maternal and Child Health Surveillance System to generate representative estimates at the national and subnational levels. In adjusting the data, we considered the sampling design and probability, applied smoothing techniques to produce stable trends, fitted livebirth and age-specific death estimates to natvional estimates produced by the UN for international comparison, and partitioned national estimates of infrequent causes produced by independent sources to the subnational level. Between 1996 and 2015, the under-5 mortality rate in China declined from 50·8 per 1000 livebirths to 10·7 per 1000 livebirths, at an average annual rate of reduction of 8·2%. However, 181 600 children still died before their fifth birthday, with 93 400 (51·5%) deaths occurring in neonates. Great inequity exists in child mortality across regions and in urban versus rural areas. The leading causes of under-5 mortality in 2015 were congenital abnormalities (35 700 deaths, 95% uncertainty range [UR] 28 400–45 200), preterm birth complications (30 900 deaths, 24 200–40 800), and injuries (26 600 deaths, 21 000–33 400). Pneumonia contributed to a higher proportion of deaths in the western region of China than in the eastern and central regions, and injury was a main cause of death in rural areas. Variations in cause-of-death composition by age were also examined. The contribution of preterm birth complications to mortality decreased after the neonatal period; congenital abnormalities remained an important cause of mortality throughout infancy, whereas the contribution of injuries to mortality increased after the first year of life. China has achieved a rapid reduction in child mortality in 1996–2015. The decline has been widespread across regions, urban and rural areas, age groups, and cause-of-death categories, but great disparities remain. The western region and rural areas and especially western rural areas should receive most attention in improving child survival through enhanced policy and programmes in the Sustainable Development Goals era. Continued investment is crucial in primary and secondary prevention of deaths due to congenital abnormalities, preterm birth complications, and injuries nationally, and of deaths due to pneumonia in western rural areas. The study also has implications for improving child survival and civil registration and vital statistics in other low-income and middle-income countries. Bill & Melinda Gates Foundation.